22a-2a+43.465=3a

Simple and best practice solution for 22a-2a+43.465=3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22a-2a+43.465=3a equation:


Simplifying
22a + -2a + 43.465 = 3a

Reorder the terms:
43.465 + 22a + -2a = 3a

Combine like terms: 22a + -2a = 20a
43.465 + 20a = 3a

Solving
43.465 + 20a = 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
43.465 + 20a + -3a = 3a + -3a

Combine like terms: 20a + -3a = 17a
43.465 + 17a = 3a + -3a

Combine like terms: 3a + -3a = 0
43.465 + 17a = 0

Add '-43.465' to each side of the equation.
43.465 + -43.465 + 17a = 0 + -43.465

Combine like terms: 43.465 + -43.465 = 0.000
0.000 + 17a = 0 + -43.465
17a = 0 + -43.465

Combine like terms: 0 + -43.465 = -43.465
17a = -43.465

Divide each side by '17'.
a = -2.556764706

Simplifying
a = -2.556764706

See similar equations:

| 3y-1+4y=8-9+7y | | 4=4(1-4x)+8(x-4) | | 3[-4-(-4+5)]= | | 3(y-8)=-y | | 7x(6x-2)=180 | | 4x=3y-7-2x | | 16y-8-8y=27 | | 10.2a+3.9=32a | | -5+h=-34 | | -4m(-7n)+(3d)(-4c)= | | 5x^2+3x-6=0 | | 4088=x(56) | | .5+.4= | | 8x+2(12x+6)= | | x+(2x-30)=150 | | 5-(5.25+3.1x)=-6.2(2.5x+1.9) | | 5(y-1)=13-y | | 2m^2-9m-35=0 | | 6(x+5)=-36 | | 4x-5(x+3)=23 | | 25-(x+7)=6x-3 | | 8-4x=-2x-4 | | 3(15x+5)-15=3(15x-15)+3 | | 9-(4+5)= | | -2x-4(-2x-2)=-10 | | 15(8-3)-64=x | | 6x+4=4x+26 | | -4x-7+6x=-6 | | 5a-2c+7=(6a-3c+2) | | -6(a+9)=-24+4a | | -6-x=-3x-2 | | p=21 |

Equations solver categories